Pengaruh Kompetensi Guru, Sarana Prasarana Pembelajaran Terhadap Semangat Kerja Guru Sekolah Menengah Pertama Negeri di Kecamatan Baguala Kota Ambon - Popy Takaria; Theresia Laurens; Lamberthus Johannes Lokollo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Improving education quality depends on teacher competence and learning facility support. This study aims to examine the influence of professional teacher competence and educational infrastructure on the work enthusiasm of public junior high school teachers in Baguala District, Ambon City. A quantitative approach with a descriptive correlational method was used. The sample consisted of 127 teachers selected via stratified random sampling. Data were collected through a closed-ended Likert scale questionnaire. The analysis revealed that teacher competence significantly influences work enthusiasm (regression coefficient = 0.379), as do facilities (coefficient = 0.271). Together, both variables explain 42.2% of the variation in teacher enthusiasm. These findings highlight the need to strengthen teacher professionalism and learning support. The study offers a foundation for integrated policy decisions to improve teacher quality. It implies the need for ongoing professional development and adequate infrastructure to ensure a productive work environment.